Integrin α2 in the microenvironment and the tumor compartment of digestive (gastrointestinal) cancers: emerging regulators and therapeutic opportunities - Liu, Tiantian; Gu, Yanmei; Zhang, Yuyu; Li, Yumin (Frontiers in Oncology, 2024)
Integrins are a family of cell surface membrane receptors and play a crucial role in facilitating bidirectional cell signaling. Integrin α2 (ITGA2) is expressed across a range of cell types, including epithelial cells, platelets, megakaryocytes, and fibroblasts, where it functions as a surface marker and it is implicated in the cell movements. The most recent findings have indicated that ITAG2 has the potential to function as a novel regulatory factor in cancer, responsible for driving tumorigenesis, inducing chemoresistance, regulating genomic instability and remodeling tumor microenvironment. Hence, we primarily focus on elucidating the biological function and mechanism of ITGA2 within the digestive tumor microenvironment, while highlighting its prospective utilization as a therapeutic target for cancer therapy.